2008
DOI: 10.3324/haematol.11644
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in induction treatment increases the very good partial response rate before and after high-dose therapy in previously untreated multiple myeloma

Abstract: In the prospective phase 3 HOVON-50/GMMG-HD3 trial, patients randomized to TAD (thalidomide, doxorubicin, dexamethasone) had a significantly higher response rate (at least PR) after induction compared with patients randomized to VAD (vincristine, adriamycin, dexamethasone, 72% vs. 54%, p<0.001). Complete remission (CR) and very good partial remission (VGPR) were also higher after TAD. After High Dose melphalan 200mg/m 2 response was comparable in both arms, 76% and 79% respectively. However, CR plus VGPR were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(83 citation statements)
references
References 21 publications
4
76
0
3
Order By: Relevance
“…[74][75][76] With the addition of a third agent, post-ASCT CR rates may reach 15% to 40%, whereas CR/VGPR rates are 50% to 75%. [77][78][79][80] However, it is clear that compared with VGPR, the CR level is associated with a better outcome. 25,81 Currently, CR defined by the absence of M-component on immunofixation and a normal bone marrow negative is the most widely accepted level.…”
Section: Which Level Of Response Is Necessary?mentioning
confidence: 99%
“…[74][75][76] With the addition of a third agent, post-ASCT CR rates may reach 15% to 40%, whereas CR/VGPR rates are 50% to 75%. [77][78][79][80] However, it is clear that compared with VGPR, the CR level is associated with a better outcome. 25,81 Currently, CR defined by the absence of M-component on immunofixation and a normal bone marrow negative is the most widely accepted level.…”
Section: Which Level Of Response Is Necessary?mentioning
confidence: 99%
“…Thalidomide is active in MM [3][4][5][6][7] and produces little hematologic toxicity, indicating that it may be preferred for use as induction therapy. 8 Previous studies evaluating thalidomide, as a component of induction therapy, have shown that it improves response rates 3,4,6,[9][10][11][12] and progression-free survival (PFS), 4,6,10,12,13 and provides similar 10,12,13 or improved 6 overall survival (OS) rates versus non-thalidomidecontaining regimens. Thalidomide also appears to be well tolerated in this setting and is associated with an acceptable rate of adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…22 Because of the limitations of our data set, it was not possible to discern an effect of differing induction regimens in this analysis, although published data in fact suggest that improved CR rates are more evident with the introduction of novel agents throughout the 2000s. [23][24][25][26] Alternatively, it is possible that this represents a technical issue of data collection and verification, as defining relapse as time points can be less definitive than defining death, features that underpin the calculation of PFS and OS, respectively. However, the reduced TTNT in 2005 compared with 1999 suggests that, in fact, the reduced time to relapse is clinically evident.…”
Section: Discussionmentioning
confidence: 99%